LEXICAL-SEMANTIC ANALYSIS OF "FREEDOM" CONCEPT IN ENGLISH, UZBEK AND RUSSIAN LANGUAGES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The following article analyses the emergence and the usage of “freedom“ concept in several languages such as in English, Uzbek and Russian. In addition, the results of online survey is defined as well. Linguistic nature of the world belonging to nations is given from conceptual and lexical point of view.